Proceedings of condensed papers - 468514 Two-Phase Flow and Heat Transfer Symposium - Workshop, Fort Landerdale, Fla., October 18-19, 1976; Veziroglu, T. Nejat (Coral Gables, Fla. : university of Miami, 1976)
05